2021
DOI: 10.1155/2021/5589505
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Personalized Service System of University Library Based on Internet of Things Technology

Abstract: In library applications, radio frequency indentification (RFID) technology, sensors, and wireless transmission networks have been applied to various services such as self-service checkout and return systems, electronic reader cards, intelligent bookshelves, intelligent monitoring of library premises, augmented reality (AR) interactive picture books, physical corridors, and seat reservations; in regional library alliances, real crossregional and cross-system alliance cooperation through IoT technology is also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Technologies such as the IoT may thus be used to create an academic library infrastructure of components and services that are intelligent, interconnected, and efficient. However, Zhuang (2021) warns that irrespective of technology evolution and usage, library principles must always be considered in terms of people oriented, reading-centred, and service-oriented focus. For Yu et al (2019) it is therefore important that academic libraries use technologies related to RFID, the IoT, image and speech recognition, and other AI technologies to offer a holistic composition of services.…”
Section: Services Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…Technologies such as the IoT may thus be used to create an academic library infrastructure of components and services that are intelligent, interconnected, and efficient. However, Zhuang (2021) warns that irrespective of technology evolution and usage, library principles must always be considered in terms of people oriented, reading-centred, and service-oriented focus. For Yu et al (2019) it is therefore important that academic libraries use technologies related to RFID, the IoT, image and speech recognition, and other AI technologies to offer a holistic composition of services.…”
Section: Services Peoplementioning
confidence: 99%
“…Hoy (2015) states that protocol standards are imperative to ensure full interoperability between objects linked to the internet. The Zigbee Alliance has for example produced a set of standards for the creation of WSNs (Cooper & James 2009), whilst standardisation of machine-to-machine communications (M2M) has secured the establishment of technical standards for interoperability related to architecture, security, and machine-to-machine reading (Mehmood, Ahmad, Yaqoob, Adnane, Imran, & Guizani 2017;Zhuang 2021). Of particular importance to offer smart library services and resources, is the IP.…”
Section: Internet Of Things Architecture Within the Context Of Academ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be shown that the larger the fit value is, the greater the likelihood that the matching meal position will be selected in the future. As a result, the meal location is determined by a game of roulette, and a new candidate solution v i is formed for the selected individual by utilizing equation (6). If the fitness value of v i is better than x i , then it is replaced, otherwise it remains unchanged.…”
Section: Mixed Continuous Ant Colony Optimization Algorithmmentioning
confidence: 99%
“…In today's world, university intelligent libraries are still in their infancy and development stages; the infrastructure has not been fully developed, the number of intelligent devices, the types of intelligent services, and the level of intelligence have all been developed but are still in their infancy and development stages, and the level of intelligence has not yet reached a significant level. University libraries should pay particular attention to the creation of wisdom libraries, optimize and improve the administration and services provided by wisdom libraries, and provide users with a wise, accurate, and human-centered wisdom service and environment that is individualized and ubiquitous [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%